The Tradition of Black Goat Slaughtering at the Beginning of Suro: An Analysis from the Perspective of Islamic Law - Baedhowi; Nur Amin; Syed Iftikhar Ali Gilani (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study examines the tradition of slaughtering black goats at the beginning of the month of Suro, a practice that remains strongly preserved in Dusun Sarangan, Campurejo Village, Tretep District, Temanggung Regency. As part of the Javanese New Year celebration, the tradition involves the ritual selection of black goats with specific criteria, such as being male, young, and having intact horns. The meat is prepared and distributed to neighbors and relatives, reflecting the communal and charitable dimensions of the practice. Using a qualitative case study approach through interviews, observation, and documentation, the study reveals that the tradition embodies expressions of gratitude to Allah, ritual devotion, and social charity. From the perspective of Islamic law, the slaughtering of black goats is considered permissible insofar as it is motivated by charitable intentions and conducted in accordance with Islamic legal principles. Beyond its religious significance, the tradition also contributes to social cohesion and resource redistribution within the community. The findings highlight the importance of understanding local values while maintaining a balance between preserving cultural heritage and responding to contemporary social change.